Self-Consolidating Concrete Produced With Fine CDW - Stéphanie Rocha (2022)
Self-consolidating concrete is a concrete technology that seeks to simultaneously achieve fluidity, passing ability and segregation. In its manufacture there is the possibility of using alternative materials, such as ground ceramic, predominantly in construction and demolition waste. Therefore, this study aims to analyze the feasibility of this concrete regarding its properties in the fresh and hardened state when there is replacement of fine sand by ground ceramic aggregate. For this, the flowing tests, flow time, visual stability index, J ring, L box, V funnel and the molding of specimens in three different compositions were carried out, one being the reference compositions and the other two with replacements of 25 and 50% in the natural fine sand by the ceramic waste sand. The mixes in which the replacements were carried out presented good fluidity, without of segregation, however, the passing ability of the mix with 50% of replacement did not fit within the recommended range. (c) 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.